2023
DOI: 10.1002/adfm.202307474
|View full text |Cite
|
Sign up to set email alerts
|

All‐Electrical Detection of the Spin‐Charge Conversion in Nanodevices Based on SrTiO3 2‐D Electron Gases

Fernando Gallego,
Felix Trier,
Srijani Mallik
et al.

Abstract: The Magnetoelectric Spin‐Orbit (MESO) technology aims to bring logic into memory by combining a ferromagnet with a magnetoelectric (ME) element for information writing, and a spin‐orbit (SO) element for information read‐out through spin‐charge conversion. Among candidate SO materials to achieve a large MESO output signal, oxide Rashba two‐dimensional electron gases (2DEGs) have shown very large spin‐charge conversion efficiencies, albeit mostly in spin‐pumping experiments. Here, all‐electrical spin‐injection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Various logic devices based on the dual control of the non-reciprocal charge transport by a gate voltage and the magnitude of the applied electrical field have been proposed in a very recent study [45]. In addition, the high charge-to-spin conversion efficiency of the LaO/STO system may be enhanced by the second-order response to improve the performance of scalable magnetoelectric spin-orbit devices [50], in which the combination of non-volatility and high energy efficiency can potentially lead to new paradigms for beyond-CMOS computing architectures [51]. Besides prospective device applications, it has also been suggested that the variation of the nonreciprocal charge current with the direction of the applied magnetic field can provide a means for determining the Rashba parameter of a 2DEG system [9].…”
Section: Resultsmentioning
confidence: 99%
“…Various logic devices based on the dual control of the non-reciprocal charge transport by a gate voltage and the magnitude of the applied electrical field have been proposed in a very recent study [45]. In addition, the high charge-to-spin conversion efficiency of the LaO/STO system may be enhanced by the second-order response to improve the performance of scalable magnetoelectric spin-orbit devices [50], in which the combination of non-volatility and high energy efficiency can potentially lead to new paradigms for beyond-CMOS computing architectures [51]. Besides prospective device applications, it has also been suggested that the variation of the nonreciprocal charge current with the direction of the applied magnetic field can provide a means for determining the Rashba parameter of a 2DEG system [9].…”
Section: Resultsmentioning
confidence: 99%